Large Carpenter Bees, Xylocopa spp. (Insecta: Hymenoptera: Apidae: Xylocopinae) - E. E. Grissell; Malcolm T. Sanford; Thomas R. Fasulo (EDIS)
This document is EENY-100, one of a series of the Entomology and Nematology Department, Florida Cooperative Extension Service, Institute of Food and Agricultural Sciences, University of Florida. Original publication date July 1999. Reviewed May 2003.